Glycaemic efficacy of glucagon-like peptide-1 receptor agonists and dipeptidyl peptidase-4 inhibitors as add-on therapy to metformin in subjects with type 2 diabetes-a review and meta analysis - Deacon, C. F.; Mannucci, E.; Ahrén, B. (Diabetes, obesity & metabolism, 2012)
Aims: During recent years, two strategies of incretin‐based therapy [glucagon‐like peptide‐1 (GLP‐1) receptor agonism and dipeptidyl peptidase‐4 (DPP‐4) inhibition] have entered the market for pharmacological management of type 2 diabetes. A main indication for this therapy is as add‐on to on‐going metformin therapy in subjects with type 2 diabetes who have insufficient glycaemic control with metformin alone. The aim of this study was to compare improvements in glycaemic control and changes in body weight, as well as adverse events, in comparable studies with incretin‐based therapy as add‐on to metformin. Methods: Studies having a duration of 16–30 weeks were identified from PubMed. Results: A total of 27 study groups in 21 studies fulfilled the criteria of examining incretin‐based therapy as add‐on to metformin at clinically recommended doses in patients with type 2 diabetes for 16–30 weeks; 7 of these used a short‐acting GLP‐1 receptor agonist (exenatide BID), 7 used longer acting GLP‐1 receptor agonists (liraglutide or exenatide LAR), whereas 14 studies examined DPP‐4 inhibitors. In all studies, incretin‐based therapy reduced HbA1c concentrations. The reduction in HbA1c was significantly greater in study groups with long‐acting GLP‐1 receptor agonists than with the other two groups (both p < 0.001), whereas there were no differences between exenatide BID and DPP‐4 inhibitors. Across all study groups, there was a negative linear correlation between baseline HbA1c and change in HbA1c (r = −0.70; p < 0.001). Fasting glucose also fell significantly more in study groups given liraglutide or exenatide LAR than in those given exenatide BID or DPP‐4 inhibitors (both p < 0.001). Furthermore, body weight was reduced by a similar extent in the two groups with GLP‐1 receptor agonists and was not significantly altered in the groups with DPP‐4 inhibitors. Lipids, blood pressure and heart rate were not reported consistently, which did not allow general conclusions. Adverse events were rare, apart from increased incidence of nausea and vomiting with GLP‐1 receptor agonists. Conclusion: Incretin‐based therapy efficiently improves glycaemia when added to metformin in patients with type 2 diabetes, and within 16–30 weeks there is a more pronounced reduction in HbA1c with long‐acting GLP‐1 receptor agonists (liraglutide and exenatide LAR) than with exenatide BID and DPP‐4 inhibitors, although the magnitude of the effect is dependent on the baseline values. Both strategies appear to be associated with a very low risk of adverse events, including hypoglycaemia. Finally, the injectable GLP‐1 receptor agonists also reduce body weight (whereas the DPP‐4 inhibitors are weight neutral) but are also associated with a greater incidence of gastrointestinal side effects and a tendency to increase heart rate.